Cultivating Change Agricultural Practices and Rural Society in Sikh-ruled Punjab - AZHAR RASHID KHANDAY; DR. JASVANT KUMAR YADAV (Innovative Research Thoughts, 2023)
The scholarly work titled "Cultivating Change: Agricultural Practices and Rural Society in Sikh-ruled Punjab" delves into the formative period of Sikh rule in Punjab during the 18th and 19th centuries. It does so in order to shed light on the profound changes that took place in the region's agricultural practises and rural society during this time. The purpose of this research is to investigate how the establishment of Sikh authority under the guidance of political figures such as Maharaja Ranjit Singh brought about substantial changes in agricultural practises, patterns of landownership, and socioeconomic structures. It illustrates how the Sikh rulers constructed new irrigation systems, encouraged cash crop farming, and altered land tax procedures, all of which had a dramatic influence on the agricultural environment. All three of these factors had a direct correlation with the growth of the Sikh empire. These innovations not only increased agricultural output but also reshaped the social fabric of rural Punjab. As a result of these changes, land ownership shifted, new social hierarchies emerged, and old agrarian communities were transformed. provides a detailed picture of the intricate interaction between agriculture, government, and society in Punjab when it was controlled by the Sikhs, making it a significant resource for academics and fans interested in the history of the province and the growth of its agriculture.